At weddings and wakes - McDermott, Alice 1953- (Farrar, Straus & Giroux, 1992)
Set in the Sixties, McDermott's third novel tells the story of an extended Irish-American family observed primarily through the eyes of the children, a son and two daughters. Time circles backwards and forwards around a variety of family rituals: holiday meals, vacations at the shore, the wedding of a favorite aunt. The poignant middle-aged romance that develops between the aunt, a former nun, and her suitor, a shy mailman, exacerbates already pronounced family tensions. As they listen to oft-repeated stories about poverty, disease, and early deaths, the children are solemn witnesses to the Irish immigrant experience in America. By turns wry and sad, this is McDermott's finest novel to date. Highly recommended.